2018
DOI: 10.6007/ijarbss/v8-i3/3934
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influenced the Problem of Truancy among Secondary School Students

Abstract: This study aims to identify the factors that influenced truancy among the students in Federal Land Development Authority (FELDA) in a secondary school in Pahang. This study was conducted on 200 respondents consisting of 52 students from Form One, 118 students from Form Two and 30 students from Form Four. These respondents have truancy records that have been identified by the school administrators. The respondents' gender have been selected randomly. The researcher had used the method of observing using the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Peers are able to influence each other in a positive manner (Steinberg, 1996). In fact, Abdullah, Salim, and Arip (2018) reported that peer influence is one of the factors that influences truancy in schools. According to Ha and Harpham (2005) there is a contextual effect of one parent's need to send her child for private tutoring on other parents' need to do the same.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Peers are able to influence each other in a positive manner (Steinberg, 1996). In fact, Abdullah, Salim, and Arip (2018) reported that peer influence is one of the factors that influences truancy in schools. According to Ha and Harpham (2005) there is a contextual effect of one parent's need to send her child for private tutoring on other parents' need to do the same.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students have to compete to enrol in public universities, to get scholarships, and to gain a chance to further their studies overseas. Yan-Li, Roslan, Abdullah, and Abdullah (2018) suggest that families play a crucial role in adolescent school performance.…”
Section: Introductionmentioning
confidence: 99%
“…Other than truancy, children's most frequent disciplinary problems in schools are bullying, theft, possession of prohibited items in schools, gangsterism (Tie, 2012), and vandalism (Zainal & Mohamad Salleh, 2008). Among factors that have been cited that contributed to truancy among children in secondary schools are personal factors such as lack of motivation (Sueb & Izam, 2016;Abdullah, et al 2018) and self-limitation such as lack of language proficiency, lack of religious knowledge and impulsive behaviour (Sueb & Izam, 2016;Nik Ruzyanei et al 2009). Closely related to personal factors that contribute to truancy among children in school is family factors such as lack of family support, low socio-economic background and broken families (Nik Ruzyanei et al 2009;Sueb & Izam, 2016;Abdullah, et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among factors that have been cited that contributed to truancy among children in secondary schools are personal factors such as lack of motivation (Sueb & Izam, 2016;Abdullah, et al 2018) and self-limitation such as lack of language proficiency, lack of religious knowledge and impulsive behaviour (Sueb & Izam, 2016;Nik Ruzyanei et al 2009). Closely related to personal factors that contribute to truancy among children in school is family factors such as lack of family support, low socio-economic background and broken families (Nik Ruzyanei et al 2009;Sueb & Izam, 2016;Abdullah, et al 2018). In addition, environmental factors such as teachers' negative attitudes towards children in school also make them feel not valued.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation